Pengaruh Kepuasan dan Loyalitas Pelanggan Terhadap Layanan Jasa Pembayaran (QRIS): (Studi pada Usaha Dkriuk Fried Chicken Tangerang-Serang) - Vera Maria; Afrian Setiawan; Agung Farrel Ramdhani; Finanti Ayu Fadhillah; Naswha Nurika Putri (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to identify the satisfaction and loyalty of Dkriuk Fried Chicken customers to financial services (QRIS) in the Serang and Tangerang areas. QRIS payment services greatly facilitate customers in payment transactions. This research uses quantitative methods by administering questionnaires to Dkriuk Fried Chikencustomers. Data from questionnaires that have been collected are analyzed using a descriptive statistical analysis approach to determine the level of customer satisfaction and loyalty to QRIS payment services at Dkriuk businesses in the Tangerang - Serang area. The results showed that QRIS payment services at the Dkriuk Fried Chiken business had a positive impact on its customers. Customer satisfaction with QRIS payment services can be seen from the ease of paying and customer loyalty can be seen from their sense of security in payment.